Ionic Liquids as Heterogeneous and Homogeneous Catalysts for Condensation and Esterification Reactions - Dong, Bing; Song, Hang; Zhang, Wei; He, Ai; Yao, Shun (Current Organic Chemistry, 2016)
At present, ionic liquids (ILs) are playing a more and more important role in organic synthesis as green catalysts and solvents. At the same time, researchers from both academia and industry have great interests in the related application of new ILs with unique structural features. Many neutral and acidic ionic liquids were used to catalyze condensation and esterification processes, which are two important reactions in fine chemical, material, energy and pharmaceutical industry. Compared with traditional catalysts, these ionic liquids have shown special advantages and potential due to their ideal catalytic performance and the unusual characteristics. For instance, temperature-sensitive ILs can automatically form a liquid-solid two phase system so it can be recovered easily from the reaction system after the synthetic process is completed, and the advantages of heterogeneous and homogeneous catalysis can be achieved simultaneously. On the basis of our recent study and latest development, the paper reviews the current application and related catalysis mechanism of ILs in above reactions in detail, especially for those with new structures. Moreover, the development trend and challenges in the further use of ILs are also discussed. It is expected to provide meaningful reference for involved researchers.
Keywords: esterification